Sarcomas of the breast. Issue 8 (August 2012) - Lahat, Guy; Lev, Dina; Gerstenhaber, Fabian; Madewell, John; Le-Petross, Huong; Pollock, Raphael E
Sarcomas of the breast are a rare group of heterogeneous mesenchymal tumors accounting for less than 1% of all breast malignancies. Owing to the rarity of the disease, current knowledge is mostly based on numerous case reports and relatively small retrospective series; unlike epithelial breast cancer, there is no high level evidence to support a standard of care for primary and/or adjuvant therapy. To overcome this relative shortage of data, most therapeutic strategies for breast sarcoma are extrapolated from current treatment for soft tissue sarcoma in other locations, mainly of the extremities and thoracic wall. In general, the therapeutic approach to sarcoma of the breast should be based on a multidisciplinary strategy including surgery, radiation to improve local control and systemic chemotherapy in selected patients. This review discusses the results of the key larger retrospective studies including data on incidence, etiology, presentation, diagnosis, management and prognosis of this challenging rare disease entity.